2016
DOI: 10.1016/j.yexcr.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Noscapine chemosensitization enhances docetaxel anticancer activity and nanocarrier uptake in triple negative breast cancer

Abstract: Chemosensitization and enhanced delivery to solid tumor are widely explored strategies to augment the anticancer efficacy of existing chemotherapeutics agents. The aim of current research was to investigate the role of low dose Noscapine (Nos) in potentiating docetaxel cytotoxicity and enhancing tumor penetration of nanocarriers. The objectives are; (1) To evaluate the chemo-sensitizing effect of Nos in combination with docetaxel (DTX), and to elucidate the possible mechanism (2) To investigate the effect of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…In our recently published study, we have evidently showed that Nos treatment lead to the activation of early stress markers such as phospho p38 and phospho JNK (family of MAP kinases) in a time and dose dependent manner, thus may sensitize TNBC cells to DTX to induce apoptosis significantly. In the same study, we published that Nos could act as an anti-fibrotic agent and enhance the tumor penetration of coumarin-6 loaded PEGylated liposomes in triple negative breast cancer xenografts 32 .…”
Section: Introductionmentioning
confidence: 87%
“…In our recently published study, we have evidently showed that Nos treatment lead to the activation of early stress markers such as phospho p38 and phospho JNK (family of MAP kinases) in a time and dose dependent manner, thus may sensitize TNBC cells to DTX to induce apoptosis significantly. In the same study, we published that Nos could act as an anti-fibrotic agent and enhance the tumor penetration of coumarin-6 loaded PEGylated liposomes in triple negative breast cancer xenografts 32 .…”
Section: Introductionmentioning
confidence: 87%
“…[27] A low dose of the benzylisoquinoline alkaloid noscapine acted as a chemosensitizer for docetaxel on triple negative breast cancer cells. [9] These results showed the promising use of natural compounds associated with chemotherapeutic agents already clinically used to overcome chemoresistance and to enhance the drug sensitivity.…”
Section: Discussionmentioning
confidence: 95%
“…Such efforts are motivated by their chemosensitizing or synergetic/additive effects against malignant tumors . In this context, bioactive compounds from natural products have been explored to act as potent chemosensitizer in combination with conventional chemotherapeutic drugs . This strategy can offer several benefits such as overcoming limitations with existing chemotherapeutic regimes by reducing the dosage required and consequently, the side effects of the chemosensitizing agent used.…”
Section: Introductionmentioning
confidence: 99%
“…In order to identify and confirm various markers involved in the cytotoxicity by the co-delivery, we carried out the western blotting for apoptotic markers in A549 and H460 cells (40). Protein markers of cell survival and apoptosis were evaluated.…”
Section: Discussionmentioning
confidence: 99%